2005
DOI: 10.1111/j.1600-0579.2004.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuing professional development – global perspectives: synopsis of a workshop held during the International Association of Dental Research meeting in Gothenburg, Sweden, 2003. Part 1: access, funding and participation patterns

Abstract: There appears to have been little previous research interest in continuing professional development (CPD) of dentists and the oral health team. This paper presents data and information on the following aspects of CPD in 17 countries in Asia, Australasia, Europe and North America: availability of different types of CPD, its providers, data on uptake of CPD courses and activities, and funding of CPD. The results indicate that lectures and hands-on skills courses were held in all 17 countries but the use of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…The modes commonly reported include: courses (including hands-on, seminars and lectures); reading journals or books; e-learning/internet usage; distance learning; and audit (8,38,54). The General Dental Council (GDC) surveyed dentists' opinions shortly after the introduction of mandatory CPD in the UK and found that commonly respondents thought that effective methods of verifiable CPD included reading journals (93%) lectures (89%), and hands-on courses (88%).…”
Section: Continuing Professional Development Modes Of Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The modes commonly reported include: courses (including hands-on, seminars and lectures); reading journals or books; e-learning/internet usage; distance learning; and audit (8,38,54). The General Dental Council (GDC) surveyed dentists' opinions shortly after the introduction of mandatory CPD in the UK and found that commonly respondents thought that effective methods of verifiable CPD included reading journals (93%) lectures (89%), and hands-on courses (88%).…”
Section: Continuing Professional Development Modes Of Deliverymentioning
confidence: 99%
“…CPD creates challenges, not least for the quality assurance of courses and programmes (19,20) as well as the need for international recognition of activities (16). Over-prescription beyond the inclusion of core topics risks de-motivating practitioners (84).…”
Section: Redwood Winning Et Al (61)mentioning
confidence: 99%
“…Those in rural areas found accessing CPD harder. CPD creates challenges, not least for the quality assurance of courses and programmes (19,20) as well as the need for international recognition of activities (16). Over-prescription beyond the inclusion of core topics risks de-motivating practitioners (84).…”
Section: Irelandmentioning
confidence: 99%
“…26,500 were dis tributed in one year alone (the fi nancial year 2001/2002). 26 They are unique in terms of the rigorous pre-distribution evaluation and assessment, wide range of topics covered and numbers distrib uted: all promoted (and promote) inter active learning.…”
Section: Cd-roms For Use In Dental Continuing Professional Developmentmentioning
confidence: 99%